PELATIHAN PEMBUATAN PRODUK BANDENG CABUT DURI BAGI MASYARAKAT PESISIR DESA HURIPJAYA, KECAMATAN BABELAN, KABUPATEN BEKASI - Pramono Adi, Catur (JURNAL KASTARA, 2022)
In 2021, the Fishery Product Processing Engineering Study Program of the Karawang Marine and Fisheries Polytechnic has carried out community service activities by applying innovations in processing burr milkfish products. The implementation of community service activities was carried out in Hurip Jaya Village, Babelan District, Bekasi Regency. Hurip Jaya Village is one of the marine tourism villages in Bekasi Regency and has a Fish Auction Place (TPI Hurip Jaya) and a large pond area. The purpose of this community service activity is to improve the community's ability to process milkfish so that it can produce products with added value. Community Service Activities in 2021 independently by Lecturers of the Fishery Product Processing Engineering Study Program (TPPP) were carried out in the community of Hurip Jaya Village, Babelan District, Bekasi Regency on March 23, 2021. The implementation method was carried out through a lecture-based approach and practice, where this activity was carried out using demonstrations as learning media and practical activities accompanied by assistance, planning and monitoring and evaluation of all community service activities. There were 10 participants in this activity as a fulfillment of the health protocol to prevent the transmission of COVID 19. Each participant was given tools and materials to practice the manufacturing method which was demonstrated by the teaching team. Evaluation is carried out orally after the material is given to determine the extent to which participants can absorb the information provided.